Critical Analysis of Catholic Media Discourse on Health Education as a New Subject in Polish Schools - Stek-Łopatka, Natalia (Przegląd badań edukacyjnych, 2025)
Health education, as a process of learning a sense of responsibility for one’s own health and the health of others, functions in many countries around the world. In 2024, a regulation was issued containing a draft curriculum for a new subject in Polish schools – Health Education. This is a manifestation of gradual legislative efforts aimed at change in Polish education. According to the concept of Michael W. Apple, groups exerting influence on the shaping of educational policy include, among others, religious groups, including those with a conservative orientation. This, in turn, may lead to the creation of inequalities in society. Therefore, the aim of this article was to reconstruct Catholic media discourse (giving voice to representatives of Catholicism) on Health Education as a new subject in Polish schools. The study was guided by the following research question: How is Health Education, as a new school subject, presented in Catholic media discourse? Thirty articles were analysed (radiomaryja.pl, opoka.org.pl, deon.pl, ekai.pl, gosc.pl), using critical discourse analysis in the discourse-historical approach of Ruth Wodak and Martin Reisigl. Supporting concepts were childhood innocence and health/morality binary. Health Education, as a new subject in Polish schools, was presented in the analysed discourse in a rather unambiguous, negative way. Catholic media equated it with sex education, seeing it as indoctrination and a threat to defenceless students, and even to the entire nation. The reasons for the negative assessment of health education in Catholic media discourse also included the departure by the authors of the curriculum from traditional values, in favour of an approach focused on scientific knowledge, and the neglect of the aspect of teacher preparation for teaching the new subject. The pressure presented in the analysed discourse ultimately proved effective – health education was no longer made compulsory. This suggests that the influence of religious groups (particularly Catholic ones) on education in Poland does, in fact, exist.